Some Biochemical and Histopathological Changes in Liver of Pregnant Female Rats Following Fluoroquinolones Administration - Ashwaq Jabbar Al-Miahy (مجلة علوم ذي قار, 2019)
The present study was designed to investigate the possible effects of fluoroquinolones (Norfloxacin, Ciprofloxacin, and Enrofloxacin) on some biochemical and histopathological changes of liver in pregnant female rats (Ratus norvigicus). 40 pregnant rats weighing 175-185 gm, and 10-12 weeks old in age, were divided equally in to control and three experimental groups. Control group treated with dimethylsulphoxide (DMSO) at a dose 0.5 ml/animal/day while the experimental animals treated with oral doses of (700 mg/Kg b.w. of Norfloxacin, 550 mg/Kg b.w. of Ciprofloxacin, and 750 mg/Kg b.w. of Enrofloxacin, all groups were administered these substances from the day 1 till the day 15 of gestation. Dissection was performed on day 15 of gestation after 4 hours from the last dose. Results revealed a significant (p<0.05) decrease in total protein content in serum of the treated groups (NFX, CPX) when compared with control, while ENX treated group showed a decrease in total protein but not significant. Assessment of globulin in all treated groups showed a significant decrease as compared with the globulin of control. Histopathological changes in liver sections of these females were in the form of dilatation of central and portal vein, and sinusoidal spaces, congestion in blood vessels, degenerated hepatocytes with necrotic nuclei. These results revealed the toxic effects of fluoroquinolones on the livers of pregnant female rats.